Using mixed method approach in measuring effects of training in firms: Case study of the European Social Fund support - Pelucha, Martin; Kveton, Viktor; Potluka, Oto (Evaluation and program planning, 2019)
Public support of training in firms corresponds to the long-term importance of the quality of human capital in the competitiveness of firms and nations. Thus, the EU supports such training via the European Social Fund (ESF). The evaluation community evaluates the support by using either qualitative or quantitative methods. The simultaneous application of these two approaches is rare. The purpose of this paper is to combine quantitative (counterfactual impact evaluation) and qualitative (qualitative comparative analysis) methods in order to fill the methodological gap. Based on the combination of both approaches, it explores their strengths, complementarity and disadvantages to evaluate public support for employee training in the Czech Republic. The combination of methods makes it possible to identify not only the impacts but also their causes. Linking the ESF support to corporate competitiveness is crucial for demonstrating the effectiveness of public spending.
Keywords: doškolování; Česká republika; výzkumný projekt; Inservice Training; Czech Republic; zaměstnanost; hodnocení programu; Causality; Organizational Case Studies; kauzalita; lidé; Program Evaluation; Research Design; Employment; případové studie organizací; financování vládou; Humans; Financing, Government